Longitudinal patterns of urinary incontinence and associated predictors in women with type 1 diabetes. Issue 1 (21st October 2021) - Bakre, Shivani; Holt, Sarah K.; Oerline, Mary; Braffett, Barbara H.; Pop‐Busui, Rodica; Wessells, Hunter; Sarma, Aruna V.
Abstract: Aims: Urinary incontinence (UI) in women is a dynamic condition with numerous risk factors yet most studies have focused on examining its prevalence at a single time. The objective of this study was to describe the long‐term time course of UI in women with type 1 diabetes (T1D). Methods: Longitudinal data in women with T1D were collected from 568 women in the Epidemiology of Diabetes Interventions and Complications (EDIC) study, the observational follow‐up of the Diabetes Control and Complications Trial (DCCT) cohort. Over a 12‐year period, participants annually responded to whether they had experienced UI in the past year. Results: We identified four categories of UI in this population over time: 205 (36.1%) women never reported UI ( no UI ), 70 (12.3%) reported it one or two consecutive years only ( isolated UI ), 247 (43.5%) periodically changed status between UI and no UI ( intermittent UI ), and 46 (8.1%) reported UI continuously after the first report ( persistent UI ). Compared to women reporting no/isolated UI, women displaying the intermittent phenotype were significantly more likely to be obese (OR: 1.86, 95% CI 1.15, 3.00) and report prior hysterectomy (OR: 2.57, 95% CI: 1.39, 4.77); whereas women with persistent UI were significantly more likely to have abnormal autonomic function (OR: 2.36, 95% CI: 1.16–4.80). Conclusions: UI is a dynamic condition in women with T1D. Varying risk factors observed for the different phenotypes of UI suggest distinctive pathophysiological mechanisms. These findings have the potential to be used to guide individualized interventions for UI in women with diabetes.